Factors Influencing the Intention of Catholic Brides and Grooms to do the Premarital HIV Test as an Attempt to Prevent HIV/AIDS in Semarang City - Hillary Jeany Alfaresedes; Zahroh Shaluhiyah; Antono Suryoputro (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2021)
Semarang Health Office in 2019 recorded the age group of 25-49 years old as the most group of people with HIV. Ironically, the productive age group is the asset of the nation, also considered as the ideal group for marriage so that premarital preparation is required to result in a healthy household. On the other hand, Catholic Church has a requirement for brides and grooms to participate in Wedding Preparation Course (KPP) and is expected to increase knowledge about the household readiness as well as encourage a willingness to do the premarital HIV test as a step of wedding preparation. This study aims to analyse factors influencing the intention of catholic brides and grooms to do the premarital HIV test. The results of the study showed that the variables that influenced the intention to do premarital HIV test were knowledge (α=0.005), behavioural beliefs (α=0.004), attitude (α=0.002), subjective norms (α=0.002), and behaviour control (α=0.007). The results of multivariate analysis showed that the most influential variables were knowledge (OR=5.222), continued by subjective norms (OR=4.631), and behavioural beliefs (OR=3.825). It is suggested that KPP can collaborate with Health Office, AIDS Commission (KPA), or Non-Governmental Organization (LSM) by conducting a sharing session.